Research of the Motivation and Long-Term Objectives of Students Participating Football and Aerobic from UNWE - Gadzhev, Milen; Stoilov, Ivan; Ignatova, Milena; Barova, Iva (Research Papers, 2021)
Education is an activity requiring lengthy efforts and perseverance, as well as skills for acquiring information and its creative usage. Long-term objectives serve as coordinating terms leading to particular goals in the everyday life and thus, behaviour could be rationalized and directed in a longer prospective towards both the past and the future. The aim of the present study is to survey the opinion and personal assessment of the long-term motivation of students from UNSS, Sofia. The results of the study were processed mathematically and statistically by: variational analysis; relative share; comparative analysis of two independent samples using Man Whitney's U-test and comparative analysis of the frequency distributions with χ² - the Pearson criterion. According to the generalized conclusions, a higher percentage of the students is directed towards long-term objectives and prospects. Women are more motivated in their long-term development than men but there are not statistically significant differences along all the questions. Students motivation is higher than the average one for the whole population. We believe, however, that the motivation changes in the course of the studies and we assume it is higher for the students who are about to graduate.
Keywords: Long-term objectives; Motivation and education; Students